Reconfigurable Reflectarray Antenna: A Comparison between Design Using PIN Diodes and Liquid Crystals. (29th October 2021) - Abbasi, Muhammad Inam; Ismail, Muhammad Yusof; Kamarudin, Muhammad Ramlee; Abbasi, Qammer H.
Abstract : This work presents the design and analysis of active reflectarray antennas with slot embedded patch element configurations within an X -band frequency range. Two active reflectarray design technologies have been proposed by digital frequency switching using PIN diodes and analogue frequency tuning using liquid crystal-based substrates. A waveguide simulator has been used to perform scattering parameter measurements in order to practically compare the performance of reflectarray designed based on the two active design technologies. PIN diode-based active reflectarray unit cell design is shown to offer a frequency tunability of 0.36 GHz with a dynamic phase range of 226°. On the other hand, liquid crystal-based design provided slightly lower frequency tunability of 0.20 GHz with a dynamic phase range of 124°. Moreover, the higher reflection loss and slow frequency tuning are demonstrated to be the disadvantages of liquid crystal-based designs as compared to PIN diode-based active reflectarray designs.